TINGKAT KEBUGARAN JASMANI SISWA UPTD SD NEGERI 16 JULI DI KABUPATEN BIREUEN MENGGUNAKAN TES KEBUGARAN PELAJAR NUSANTARA (TKPN) - Hanif Taufiqurrahman; Amiruddin; Masyitah (lembaga Sepercenter, 2025)
Physical fitness is an essential and fundamental indicator of quality of life in supporting student learning achievement (Kuncoro Darumoyo et al., 2025). This quantitative descriptive study aims to examine the physical fitness levels of 50 students in grades 4, 5, and 6 at UPTD SD Negeri 16 Juli, Juli District, Bireuen Regency, using the Nusantara Student Fitness Test (TKPN) instrument. TKPN, launched by the Ministry of Youth and Sports in 2022, is designed to measure students' physical ability to carry out daily activities without experiencing excessive fatigue (Sutoro et al., 2024; Rusdiana et al., 2022). Data analysis results show that the majority of students have a nutritional status in the Good Nutrition category, but their overall physical fitness level is in the Fair category, similar to the findings in students at SDN 1 Rejomulyo (Fajaryanto et al., 2022). The Cardiovascular Endurance Component (PACER), which has a weight of 85%, is the main limiting factor (Oktavia Dewi et al., 2024). It is concluded that a structured and systematic physical activity improvement program is needed in schools to optimize student fitness (Sutoro et al., 2024; Kuncoro Darumoyo et al., 2025).